2000
DOI: 10.2105/ajph.90.4.608
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime prevalence of and risk factors for psychiatric disorders among Mexican migrant farmworkers in California

Abstract: A B S T R A C TObjectives. In this study, the prevalence of and risk factors for 12 psychiatric disorders were examined by sex and ethnicity (Indian vs nonIndian) among Mexican migrant farmworkers working in Fresno County, California.Methods. Subjects aged 18 through 59 years were selected under a cluster sampling design (n = 1001). A modified version of the Composite International Diagnostic Interview was used for case ascertainment. The effects of sociodemographic and acculturation factors on lifetime psychi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(39 citation statements)
references
References 30 publications
3
35
1
Order By: Relevance
“…Previous studies with Mexican migrants in the US have found an association between one’s ability to speak English (typically used as a proxy for acculturation) with alcohol and drug use patterns [4749]. Though ability to speak English was positively associated with at-risk drinking in univariate analyses, this relationship was not significant after adjusting for other factors.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies with Mexican migrants in the US have found an association between one’s ability to speak English (typically used as a proxy for acculturation) with alcohol and drug use patterns [4749]. Though ability to speak English was positively associated with at-risk drinking in univariate analyses, this relationship was not significant after adjusting for other factors.…”
Section: Discussionmentioning
confidence: 86%
“…Mental distress among Mexican immigrant women like María often come to a front in later age, which has been attributed to social support, worsening physical health, and other factors related to depression (Black 1999; Gerst, Al-Ghatrif et al 2010). Epidemiologists have demonstrated that Mexican-Americans report higher rates of mental distress in the United States compared to other ethnic groups, and that U.S.-born Mexican-Americans report higher rates of psychiatric distress compared to Mexican immigrants (Burnam, Hough et al 1987; Alderete, Vega et al 2000; Alderete, Vega et al 2000; Escobar, Hoyos Nervi et al 2000; Allegria, Mulvaney-Day et al 2007; Allegria, Canino et al 2008). Some have argued that this disproportionate burden of mental distress among people of Mexican descent may be attributed to poor access to mental health care and resultant chronicity of mental distress (Castañeda 2010; Gonzalez, Tarraf et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Results consistent with reports from Cantero [67] and Ebin [68] suggesting that younger Latinos may be more susceptible to negative health outcomes of acculturation including poor sleep quality. Potential causes for acculturation-associated poor sleep quality include reduced hours of sleep, irregular sleep schedules, increased use of alcohol, tobacco, and stimulants, and the social stress needed to keep up with the busy American lifestyle [55,65,[71][72][73][74][75][76][77][78][79][80][81][82][83].…”
Section: Discussionmentioning
confidence: 99%